2021
DOI: 10.1093/plphys/kiab392
|View full text |Cite
|
Sign up to set email alerts
|

Root plasticity under abiotic stress

Abstract: Abiotic stresses increasingly threaten existing ecological and agricultural systems across the globe. Plant roots perceive these stresses in the soil and adapt their architecture accordingly. This review provides insights into recent discoveries showing the importance of root system architecture and plasticity for the survival and development of plants under heat, cold, drought, salt, and flooding stress. In addition, we review the molecular regulation and hormonal pathways involved in controlling root system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
146
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(153 citation statements)
references
References 183 publications
7
146
0
Order By: Relevance
“…This concluded that ZmBES1/BZR1-3 and ZmBES1/BZR1-9 suppressed the root development, which resulted in an increase in drought sensitivity. Adjusting the root system architecture is one important clue for plants to conquer stress due to the root being the first defensive line to adapt to their environment [ 35 , 36 ]. Moreover, bes1-D had a shorter meristem size in the root [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…This concluded that ZmBES1/BZR1-3 and ZmBES1/BZR1-9 suppressed the root development, which resulted in an increase in drought sensitivity. Adjusting the root system architecture is one important clue for plants to conquer stress due to the root being the first defensive line to adapt to their environment [ 35 , 36 ]. Moreover, bes1-D had a shorter meristem size in the root [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sensing of salt stress signals by the root meristematic zone leads to a series of responses such as remodeling of root system architecture, halotropism, and abscisic acid (ABA) accumulation and translocation to the shoot, all of which ultimately result in adaptation to salinity ( Galvan-Ampudia and Testerink, 2011 ; Shabala et al, 2016 ; Karlova et al, 2021 ). Similar salt sensing and signal transduction processes may also exist in shoot cells to detect and respond to salt ions such as Na + that are transported to the shoot via the transpiration stream, but their identity and specific roles need to be further explored.…”
Section: Sensing Of Salt Stressmentioning
confidence: 99%
“…The root system architecture (RSA), as a pivotal characteristic of the root economic spectrum, refers to the complex physical connectivity belowground of plant parts (i.e., first-order, second-order, i- th-order, and primary roots), linking the root tips of different root branching, which serves as a networked channel for the circulation of plant matter, energy, and information (Karlova et al, 2021 ). Compared with the morphological characteristic of fine roots, the RSA is more important for the absorption and uptake of nutrients and water (Luo et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%